Field assessment of plant growth performance and residue persistence of saponin-based molluscicide formulations - Rosli, Nura Adila Mohd; Ismail, Siti Izera; Nasir, Nadiah Mad; Zainol, Maznah; Mokhtar, Anis Syahirah (Universiti Putra Malaysia, 2026)
This study evaluated the plant growth performance and environmental residue behaviour of saponin-based molluscicide formulations under field conditions. The findings were compared against two commercial chemical molluscicides: niclosamide and fentin acetate. Two saponin formulations, emulsifiable concentrate (EC) and wettable powder (WP) of saponin-based molluscicides, were applied at varying concentrations on rice crops, alongside chemical and water controls. Growth parameters, including plant height, tiller number, biomass, and harvest index, were recorded, while molluscicide residues were analysed in rice tissues, soil, and water using HPLC. Results showed no significant differences in growth performance among treatments. However, niclosamide exhibited the highest residue levels and most prolonged half-lives across all matrices, raising concerns over persistence and potential food safety risks. In contrast, saponin formulations demonstrated faster degradation with half-lives below 10 days and reduced environmental persistence. Despite detectable residues in polished grains, saponin is considered safe for human consumption due to its natural occurrence and rapid biodegradability. The findings supported the potential of saponin-based molluscicides as environment friendly alternatives to synthetic chemicals in rice cultivation. Further studies are recommended to improve formulation efficacy and understand their biochemical interactions with target pests.